2015
DOI: 10.15740/has/ijps/10.1/29-32
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oil formulations of Nomuraea rileyi (Farlow) Samson against Spodoptera litura under laboratory conditions

Abstract: SUMMARYThree oil formulations of entomopathogenic fungus Nomuraea rileyi were evaluated for their efficacy along with crude formulation against third instar Spodoptera litura during 2011-2012 at the Department of Entomology, S.V. Agricultural College, Tirupati. Mean larval mortalities of 96.67, 93.33, 86.67 and 76.67 per cent, respectively were recorded with groundnut, sunflower, coconut oil based formulations and crude formulation of N. rileyi at highest concentration i.e., 1 x 10 8 spores ml -1 at 10 DAT. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The larval mortality due to oil based formulations of N. rileyi was expressed as per cent mortality before subjecting to statistical analysis by using the formula (Sharmila et al, 2015).…”
Section: Analysis Of the Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The larval mortality due to oil based formulations of N. rileyi was expressed as per cent mortality before subjecting to statistical analysis by using the formula (Sharmila et al, 2015).…”
Section: Analysis Of the Datamentioning
confidence: 99%
“…At the end of 10 th day, the highest cumulative mortality of 95 per cent was obtained in oil formulations whereas 83.10 and 77 per cent mortalities were recorded with WP and crude N. rileyi respectively. Sharmila et al, (2015) evaluated oil formulations of N. rileyi against S. litura under laboratory conditions and reported more than 70 % larval mortalities of S. litura in case of groundnut and sunflower oil based formulations with concentrations above 1x 10 6 spores per ml and mortality reduced with concentrations showing least with 1x 10 2 spores per ml. Prior et al, (1988) who reported that laboratory studies primarily with grasshopper have shown that oil formulation of aerial conidia of M. anisopliae are more efficacious than aqueous formulation under various temperature and moisture conditions.…”
Section: Plate1mentioning
confidence: 99%
“…Simple formulations may protect conidia from abiotic stressors, as previously reported for species in the Metarhizium anisopliae complex [15][16][17], including the negative effects of some chemical fungicides [18]. For the fungus M. rileyi, only experimental low-cost formulations have been tested under laboratory conditions [19][20][21], greenhouse [22], and field conditions [9,23]. However, information on how these formulations may protect M. rileyi conidia from the negative effects of the chemical fungicides used in soybean crops is unavailable.…”
Section: Introductionmentioning
confidence: 99%